Synthesis, characterization and antiurease activities of a novel Mannich base 1-[(4-methoxyphenyl)(2-methylidenecyclohexyl)methyl]pyrrolidine (MMP) and its complexes with Cu (II), Ni (II), Co (II), and Fe (II) ions. Issue 10 (3rd October 2017) - Liaqat, Muhammad; Mahmud, Tariq; Hameed, Abdul; Ashraf, Mohammad; Shafiq, Muhammad; Asghar, Humna
ABSTRACT: Mannich base 1-[(4-methoxyphenyl)(2-methylidenecyclohexyl)methyl]pyrrolidine (MMP) was synthesized by condensing cyclohexanone, 4-methoxybenzaldehyde, and pyrrolidine together using ethanol as solvent. The synthesized ligand was further made to react with CuCl2, NiCl2, CoCl2, and FeCl2 to afford their respective complexes. Fourier transform infrared spectroscopy (FTIR), proton nuclear magnetic resonance ( 1 H NMR), carbon thirteen nuclear magnetic resonance ( 13 C NMR), thermogravimetric analysis (TGA), and mass spectrometry (MS) were used to characterize the ligand and its complexes. The proposed geometries of the complexes were established on the basis of metal–ligand ratio through atomic absorption spectroscopy (AAS). The synthesized compounds were analyzed for their antiurease potential. Mannich base showed moderate antiurease activity with an IC50 value of 224.83 ± 0.84 μM. Complexes with Ni (II) and Fe (II) exhibited potent antiurease activity (4.41 ± 0.003, 5.21 ± 0.003 μM, respectively) while the Co (II) complex showed excellent (46.52 ± 0.05 μM) antiurease activity and poor antiurease activity was shown by the Cu (II) complex (424.32 ± 0.96 μM) as compared with the standard thiourea (21.25 ± 0.15 μM). Docking studies of the ligand were also consistent with the experimental results.